JACKETS FOR PREGNANT WOMEN (MAINTAINING THE HEALTH OF PREGNANT WOMEN) THROUGH PRENATAL YOGA AND LACTATION PREPARATION - Fatmawati, Zeny; Suryani, Lilis; Sarmin, Sukati; Sari, Wahyu Anjas; Niah, Najah Soraya; Sumini, Gempi Tri (Journal of Indonesian Public Health Service, 2024)
Pregnancy is a physiological process, but during pregnancy pregnant women need midwifery care to evaluate their health and pregnancy conditions. Midwifes a care provider who can strive to improve the mother's health during pregnancy. Prenatal yoga is able reduces the physical discomfort of pregnant women and can make the mother's mood and Nutrition is very influential on brain growth and development. Rapid brain growth occurs in 2 phases. The first phase is at 15-20 weeks of gestation and the second phase is 30 weeks to 18 months after the baby is born.. The aim of community service activities is to reduce discomfort during pregnancy and prepare the mother's body for a comfortable birth and preparation for good lactation. This service activity was carried out in the Polindes room, Waung Village, Baron District, Nganjuk Regency at 09.00-11.00 on 14 – 16 September 2023. Participants in the activity were 10 pregnant women in the third trimester. The activity began with a speech from the head of the Baron Community Health Center, followed by the practice of pregnancy yoga and education on balanced nutrition for pregnant women. As a result of this activity, pregnant women understood the importance of balanced nutrition during pregnancy and their bodies felt healthy. The importance of maintaining health through pregnancy yoga and balanced nutrition as an effort to maintain health and prepare for lactation.